2013
DOI: 10.1063/1.4810846
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence of Cu2ZnSnS4 polycrystals described by the fluctuating potential model

Abstract: The growth of Cu2ZnSnS4 (CZTS) polycrystals from solid state reaction over a range of compositions, including the regions which produce the highest efficiency photovoltaic devices, is reported. X-ray measurements confirm the growth of crystalline CZTS. Temperature and intensity dependent photoluminescence (PL) measurements show an increase in the energy of the main CZTS luminescence peak with both increasing laser power and increasing temperature. Analysis of the PL peak positions and intensity behavior demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 51 publications
(67 reference statements)
1
25
0
Order By: Relevance
“…6c and reveals a broad featureless peak centred at~917 nm (1.35 eV), similar to previous photoluminescence measurements (e.g. [8,9]). The broadness of the luminescence peak, even at 10 K temperature, makes it difficult to analyse any variations in the spectra between different sample regions using the traditional method of Gaussian curve fitting.…”
Section: Bg Mendis Et Al Solar Energy Materials and Solar Cells 17supporting
confidence: 73%
See 2 more Smart Citations
“…6c and reveals a broad featureless peak centred at~917 nm (1.35 eV), similar to previous photoluminescence measurements (e.g. [8,9]). The broadness of the luminescence peak, even at 10 K temperature, makes it difficult to analyse any variations in the spectra between different sample regions using the traditional method of Gaussian curve fitting.…”
Section: Bg Mendis Et Al Solar Energy Materials and Solar Cells 17supporting
confidence: 73%
“…In this paper we present evidence for spatially non-uniform optical properties in CZTS using cathodoluminescence (CL) in a scanning electron microscope (SEM). Photoluminescence spectra measured from bulk CZTS typically show a broad featureless peak [9], which makes it difficult to extract the underlying recombination pathways. The high spatial resolution in an SEM however provides more local information and by cooling the specimen close to liquid-He temperature the effect of phonon broadening of the luminescence peaks can also be reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite, the above characterization showing that the formed layer was likely a single CZTSe phase, the PL signal was broad at room temperature. The presence of defects or/and potential fluctuations [10] in the CZTSe structure could explain the broad PL peak since a contribution of sub-band gap recombination remains all the way up to room temperature. The fluctuating potentials could arise either from strong compensation in the material or from stoichiometry variations leading to band gap variation inclusions in the main kesterite absorber material.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in the case of polycrystalline semiconductors, local disorder at grain boundaries causes a significant density of electronic states (tails states) within the band-gap energy [20,40,41]. Several PL studies performed on CZTS have shown that at low temperature the spectra are dominated by a broad and asymmetric band centered at around 1.2-1.3 eV as reported for single crystals [24,27,42,43], polycrystals [28,44,45], thin films [31,34,[46][47][48][49], monograin powders [50,51], and nanocrystals [52]. No agreement exists concerning the nature of involved states and also on the nature of the radiative transitions.…”
Section: Introductionmentioning
confidence: 93%